Developing an ‘ePortfolio of Evidence’ Towards Employment and Registration for Early Childhood Teachers - Pauline Roberts; Leonie Menzel; Bev Adkin; Lennie Barblett (Journal of Teaching and Learning for Graduate Employability)
ePortfolios have been in use in Initial Teacher Education (ITE) courses for many years. The link to employability has been part of these initiatives, however, recent concerns over workforce and employment requires additional focus to ensure the ongoing sustainability of the ePortfolio. Ensuring teachers are ‘classroom ready’ led to increased pressure on pre-service teachers (PSTs) to demonstrate achievement of the Australian Professional Standards for Teachers (APST) (Australian Institute for Teaching and School Leadership, 2017). The goal of this project was to explore and influence PST’s thinking towards the ePortfolio through changes in practice. The research entailed a rapid systematic review of ePortfolio practice towards employment and registration; an online survey of early childhood PSTs to identify their use of the ePortfolio; implementation of improved programs to scaffold the completion of the ePortfolio; and examination of Learning Management System Discussions from graduating PSTs to identify the benefits or changes resulting from the scaffolding processes. Although PSTs recognised that the ePortfolio should be augmented across the degree, many did not feel the need to fully engage with the platform before the submission of the ePortfolio was required for assessment. Many PSTs still appeared unaware of the connection of the ePortfolio to future employment and registration requirements.